1976
DOI: 10.1111/j.1365-2362.1976.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myocardial Revascularization Following Acute Coronary Occlusion in Pigs

Abstract: In a comparative study in pigs the extent of myocardial infarction has been estimated following a temporary three hour coronary occlusion and following a permanent coronary ligation. For evaluation of the cellular injury the infarct size has been determined by a histochemical staining procedure and correlated with serum enzyme studies (creatine phosphokinase, alpha-hydroxybutyric dehydrogenase) in the surviving animal. No significant difference could be detected between the two experimental groups and the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(2 reference statements)
5
12
2
Order By: Relevance
“…Pigs were chosen because the development of coronary anastomoses and collaterals are not subjected to wide variations found in the canine heart [ 10-121 ; moreover, the major coronary distribution and blood supply to the conduction system are similar to man [ 13, 141 . In a preliminary study we have shown that a perfusion deficit of reproducible size can be created by controlled coronary ligation in the pig [9], thus confirming the suitability of the pig heart for this experimental problem.…”
Section: Methodssupporting
confidence: 57%
“…Pigs were chosen because the development of coronary anastomoses and collaterals are not subjected to wide variations found in the canine heart [ 10-121 ; moreover, the major coronary distribution and blood supply to the conduction system are similar to man [ 13, 141 . In a preliminary study we have shown that a perfusion deficit of reproducible size can be created by controlled coronary ligation in the pig [9], thus confirming the suitability of the pig heart for this experimental problem.…”
Section: Methodssupporting
confidence: 57%
“…The preservation of ischemic myocardium by early revascularization in animal models is a controversial issue (10)(11)(12)(13)(14)(15)(16)(17). Variability in experimental results may be due to many factors, including differences in collateral flow within (18) and between…”
Section: Resultsmentioning
confidence: 99%
“…Collateral circulation in pigs is less extensive than in dogs (19), and an equivalent coronary occlusion producing primarily a subendocardial infarction in the dog, results in a transmural infarct in the pig (20). In contrast to reperfusion in dogs, reperfusion 3 h after coronary artery occlusion in pigs does not result in any salvage of the area at risk (16,17). We studied baboons because their coronary anatomy closely resembles that of man (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The suitability of the pig heart for our experimental design was demonstrated in a preliminary study, where a pefusion deficit of reproducible size could be created by controlled coronary ligation (Althaus et al, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in recent years experimental and clinical research has been increasingly directed to the measurement and control of myocardial infarct size (Althaus et a/., 1976;Hillis and Braunwald 1977; Maroko e t a / . , 1971;Yusuf and Sleight 1984).…”
Section: Introductionmentioning
confidence: 99%